Kekerasan Terhadap Perempuan Sebuah Tanggapan dari Perspektif Teologi Kristen - Firman Panjaitan; Dwi Ratna Kusumaningdyah (Logia, 2026)
This research is motivated by the persistent strength of patriarchal culture in Indonesia, which places women in subordinate positions and makes them vulnerable to violence, both in domestic and social spheres. This condition not only limits women’s roles but also affects their representation and participation in various aspects of life. The study aims to examine in depth the Christian faith’s response to violence experienced by women and to formulate contextual theological and practical solutions. The method employed is qualitative research using a literature review approach and theological-critical analysis of biblical texts and related literature. The findings indicate that Christian faith essentially affirms the equality and dignity of women. In conclusion, the church is called to take a prophetic stance, accompany victims, and promote just and equitable social transformation.